EFFECTS OF AIR INTAKE RUNNER LENGTH AND DIAMETER ON THE VOLUMETRIC EFFICIENCY OF SI ENGINE (Jurnal Teknologi (Sciences & Engineering), 2025)
The performance of an engine is majorly influenced by volumetric efficiency which is on how much air an engine cylinder can be filled. Low engine performance by low and inconsistent volumetric efficiency across different engine speeds can be due to air pressure wave flow in the intake system. Thus, in this current study, we present an approach in investigation on the impact of intake parameters aimed at maximizing Proton CamPro 1.6L SI engine performance and efficiency. The approach incorporates helmholtz resonance and wave propagation method to improve engine performance through intake system. It was expected that the study can obtained the optimized air intake length and diameter for the engine to operate at optimum efficiency. A combination of fluid flow simulation and air wave theory in 1D computation fluid dynamic were implemented to compute its behavior in the engine cycle. The simulation ran on the different range of engine speed from 1000 rpm to 6500 rpm and different design parameters based on helmholtz resonator and wave propagation method for intake runner length and intake runner diameter. The results demonstrated significant improvement at mid-range rpm which had the intake runner length improved volumetric efficiency up to 8.71% by increasing the length to 528 mm while improved up to 5.34% by decreasing the diameter to 34.7 mm. For high rpm range, volumetric efficiency improved up to 4.19% by increasing the diameter to 44.4 mm and maintaining the short runner length of 400 mm.